Efficacy of Diaphragmatic Breathing and Balloon-Blowing Load Exercises in Improving Lung Capacity Among Athlete Runners - Rofi’ Nurul ‘Aini; Slamet Riyadi; Muchsin Doewes (Bulletin of Community Engagement, 2026)
Lung capacity is an important physiological component that plays a role in the performance of middle- and long-distance runners. Breathing exercises based on strengthening respiratory muscles, such as diaphragmatic breathing and balloon-blowing load exercise have been shown to contribute to improved lung function. This study aims to analyze the effectiveness of DB and BBE in increasing lung capacity in university runners, taking into account differences in age range. The study used a 2×2 factorial experimental design with two types of exercise diaphragmatic breathing and balloon-blowing load exercise and two age categories ≤19 years and >19 years. The study sample was UNS runners selected through a total sampling technique. All participants underwent a four-week training program with a frequency of three times per week and a duration of 30–45 minutes per session. Lung capacity was measured using spirometry in the pre-test and post-test phases. The results showed that both DB and BBE provided a significant increase in lung capacity compared to baseline. BBE showed a greater increase than DB, indicating the effectiveness of expiratory load in training pulmonary ventilation capacity. The findings confirm that a diaphragmatic control-based breathing intervention and expiratory resistance can induce ventilatory adaptations relevant to a young athletic population. Analysis showed that age and training type did not significantly influence pretest and posttest responses, indicating that both intervention models have the potential for relatively universal benefits for young adult runners. Through a structured, 12-session intervention design, this study adds to the evidence that simple, inexpensive, and easy-to-implement breathing exercises can be an effective strategy for supporting athletes' respiratory function. Limitations such as the small sample size, short intervention duration, and the lack of additional mechanistic measurements suggest the need for further research to provide a more comprehensive picture. Overall, this study makes a significant contribution to the literature on respiratory training and confirms the potential of breathing exercises as an important component of a runner's physical capacity development program.